Sistema administrativo para el control de los procesos en la Empresa Florícola m&j Flowers de la ciudad de Latacunga – Cotopaxi - Vargas Vinueza, Javier Olmedo (2015)
The purpose of this project is to build an administrative system under web platform for process control in Floriculture M & J Flowers of the city of Latacunga - Cotopaxi, the same that will keep updated information of the processes that are used in departments: Production and personal control, this system will get a better effectiveness in data processing, obtaining quick and reliable information from anywhere in the world. The administrative web system has been developed using the following tools: • Microsoft Visual Studio. Net • SQL Server Database The creation of this administrative system aims, record production processes, generate reports, to improve process control in the company. The DUM methodology, which is a process of software development iterations was used, this methodology has been the key to developing each of the stages through which software is made pillar diagram types that were used for documentation software are: use case diagrams, sequence diagram, class diagram, activity diagram, conceptual model and entity relationship diagram. Once I completed all items proposed for the development of the project, concluded that it was feasible to achieve the same , to the system have been developed allow administrative control of Floriculture M & J Flowers, which may be susceptible to effect you settings according to the new requirements that have a future in the process. In summary administrative system developed for Floriculture Flowers M & J allow users of the system will bring the precise control of administrative processes that are manipulated in the business.